The Siwalik Group of Sediments at Surai Khola in Western Nepal and its Palaeontological Record - Corvinus, G. (Journal of Nepal Geological Society, 1993)
The Siwalik Group is a sequence of molasse sediment consisting of claystones, siltstones, sandstones and conglomerates deposited in the foredeep in the front of the Himalaya from later Miocene to Pleistocene times. An almost complete sequence of Siwalik Group of rocks having a thickness of about 5,500 m have been recorded in the Surai Khola area in the Western Nepal. This group of rocks have been divided into five lithological units, which show a gradual coarsening of the deposits upwards. The lithostratigraphy and biostratigraphy of the Siwalik Group of sediments occurring in the Surai Khola area have been established. Their detailed investigation yielded abundant palaeontological and environmental records which have provided much insight into the understanding of the geologic evolution and the palaeoenvironment during the deposition of the Siwalik Group.